EFFECTIVENESS AND IMPORTANT ROLE OF QRIS IN PAYMENT SYSTEMS FOR ENTREPRENEURSHIP MARKETING - Muhammad Syahid; Komang S. M Parwati; La Ode Zainudin (Adisam Publisher, 2025)
This study aims to examine the effectiveness and important role of QRIS in the payment system and its impact on entrepreneurial marketing strategies. QRIS is a simplified QR code-based payment standard that facilitates digital transactions and facilitates the integration of various payment platforms. This study analyzes how QRIS contributes to increasing customer accessibility, accelerating the transaction process, and expanding market reach for business actors, especially MSMEs. In addition, QRIS allows the collection of transaction data that supports the implementation of more targeted and efficient marketing strategies. The findings show that the use of QRIS also increases customer loyalty through digital promotions such as cashback and discounts, as well as strengthening brand awareness. Overall, this study confirms that QRIS is not only a payment tool, but also a catalyst for entrepreneurial growth in the digital era